PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPOSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN INDUSTRI MANUFAKTUR - Tri Sumiyanti; Dian Kurniasari; Sari Rahmadhani (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
Manufacturing industry currently plays an important role in meeting the needs of society. The social concern factor, namely Corporate Social Responsibility Disclosure (CSR) and governance, namely Good Corporate Governance (GCG) which is disclosed in the company's financial statements can affect the value of the company. This research was conducted to prove the role of disclosure of these two factors for the value of the company in the future. This study uses a population of manufacturing industry companies listed on the Indonesia Stock Exchange 2015-2019. The results of linear regression testing indicate that CSR disclosure has a positive effect on firm value and GCG disclosure has a positive effect on firm value. This shows that disclosure is an important thing to consider in assessing the company. The more disclosure of the value of the company will increase. The control variables in this study are cash holding, cash value and firm size, only company size has a negative effect on firm value. So that small companies are more able to increase the number of CSR and GCG disclosures compared to large companies. This shows the ability to master the conditions of small companies is more efficient and effective than large companies.